A new dawn for MSMEs and start-ups. Issue 3 (3rd July 2021) - Osman, Ahmed
ABSTRACT: Things can change quickly in life. The security of one moment can quickly become impermanent before we have a chance to realize it. This is certainly the case with the crisis that has resulted from the global outbreak of the coronavirus (COVID-19). Millions of people globally have been infected, and thousands have already died from the outbreak. The general public is advised to remain socially distant from one another and to regularly wash their hands. The global economy has gone into freefall, and a recession, if not a depression, now seems likely. Panic buying in the shops is common practice. No one knows what tomorrow holds.